A method to determine electron mobility of the two-dimensional electron gas in AlGaN/GaN heterostructure field-effect transistors. (October 2017) - Cui, Peng; Lin, Zhaojun; Fu, Chen; Liu, Yan; Lv, Yuanjie
Abstract: Taking into consideration the resistance variation in the free-contact area versus the gate bias, an applicable method to determine the electron mobility in AlGaN/GaN heterostructure field-effect transistors was presented. Based on the measured capacitance-voltage and current-voltage curves, the new method employed iteration calculation with different scattering mechanisms. Compared to the electron mobility calculated by the traditional method, the electron mobility calculated by the new method shows an apparent difference, especially for the device with a larger gate length. This difference originates from the device with a larger gate length that has a stronger polarization Coulomb field scattering. At last, the correctness and necessity of this method was demonstrated by the comparison between the experimental and calculated transconductance values. Highlights: A new method to determine the electron mobility was presented. The resistance variation in the free-contact region was taken into account. The new method will be more meaningful with the device scaling.